Pengaruh Pendidikan Perempuan dan ICT terhadap Partisipasi Angkatan Kerja Perempuan di Negara Anggota OKI - Husein, Farid; Aswin, Tika Arundina (Universitas Negeri Padang, 2025)
In recent decades, OIC member countries have faced low female labor force participation rates, influenced by various factors, such as education, fertility, income, norms, and culture. One strategy to increase this participation is to improve the quality and quantity of women's education and the utilization of ICT, particularly the Internet. Information and Communication Technology (ICT) is the fusion of various sectors, especially in services and manufacturing, involving sending, retrieving, or delivering information and data electronically. This study aims to identify the effect of education moderated by ICT utilization, especially the Internet, on female labor force participation in high- and low-income OIC member countries, utilizing secondary data from 2008 to 2021. This research method uses a panel data approach with fixed effect model estimation. The results show that ICT positively affects female labor force participation driven by women's education and sound financial development in high-income OIC member countries. In low-income OIC countries, education has not been able to encourage the role of ICT to increase female labor force participation. In low-income OIC member countries, ICT, with good financial development, can increase women's labor force participation. OIC member countries need to increase investment in ICT access and infrastructure, especially in low-income countries, and improve the quality of education and financial development to support the utilization of ICT in encouraging women's labor force participation.